Correction: Flexible and highly stable electrospun nanofibrous membrane incorporating gold nanoclusters as an efficient probe for visual colorimetric detection of Hg(ii). Issue 12 (28th March 2015) - Senthamizhan, Anitha; Celebioglu, Asli; Uyar, Tamer
<x xml:space="preserve">Abstract</x> Correction for 'Flexible and highly stable electrospun nanofibrous membrane incorporating gold nanoclusters as an efficient probe for visual colorimetric detection of Hg(ii)' by Anitha Senthamizhan et al., J. Mater. Chem. A, 2014, 2, 12717–12723.